2008
DOI: 10.1111/j.1469-5812.2007.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Theory and the Philosophy of Education

Abstract: Following a brief introduction to complexity theory, this paper considers how various themes in the field relate to the philosophical study of education. Issues and questions introduced include the challenge of complexity theory for the philosophy of education-and, conversely, some critical challenges for complexity theory from educational philosophy; complexity theory and educational continuity and change; the importance that complexity theory places on interpretive perspectives that are transphenomenal, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 4 publications
1
55
0
4
Order By: Relevance
“…A Berkeley study of one thousand graduate students (Mason 2008) demonstrated a significant gender gap of 10 per cent between male students who saw an academic career, and female students who saw choices between having children and being a research professor, of more likely moving to follow a partner and being less able to maintain sustained research, and therefore more likely to be in teaching. Furthermore, female graduates are much more likely than their male counterparts to complete their PhD as a solo project and less likely to be part of a research group and to pursue their PhD for intrinsic motivations such as intellectual and academic development, personal satisfaction, or interest rather than career (Dever et al 2008).…”
Section: The Next Generation?mentioning
confidence: 99%
“…A Berkeley study of one thousand graduate students (Mason 2008) demonstrated a significant gender gap of 10 per cent between male students who saw an academic career, and female students who saw choices between having children and being a research professor, of more likely moving to follow a partner and being less able to maintain sustained research, and therefore more likely to be in teaching. Furthermore, female graduates are much more likely than their male counterparts to complete their PhD as a solo project and less likely to be part of a research group and to pursue their PhD for intrinsic motivations such as intellectual and academic development, personal satisfaction, or interest rather than career (Dever et al 2008).…”
Section: The Next Generation?mentioning
confidence: 99%
“…For example, the distance along a meandering stream channel is related to the length of the ruler used to measure it; there is no unique answer but rather a relationship. Educators and education researchers are beginning to embrace complexity theories as the bases for new ways of thinking about what we teach and how we teach (e.g., Davis and Sumara 2006;Doll et al 2008;Mason 2008). By confronting the contradictions in our worldview and being guided by such theories, we and our students might begin to see things in radically new ways.…”
Section: Lessons Learned and Recommendationsmentioning
confidence: 99%
“…Since the late 1990s an alternative view of teaching and learning has begun to attract significant interest, the idea of complexity theory (Morrison 2002, Davis and Sumara 2006, Mason 2008. Complexity theory maintains that many natural and social systems are not composed of simple, linear relationships but are instead formed from complex processes which cannot be understood by recourse to reductive analysis.…”
Section: Classrooms As Complex Phenomena: the Quantifiable Conundrummentioning
confidence: 99%